The lack of specificity of sodC-based PCR for the detection of Neisseria meningitidis carriage in pharyngeal swabs from adolescents - Dan Duy Pham-Tran; Lex E. X. Leong; Mark McMillan; Andrew Lawrence; Hassen Mohammed; Adam Finn; Helen S. Marshall (Microbiology Spectrum)
ABSTRACT The utility of the superoxide dismutase C (sodC) gene for detecting Neisseria meningitidis carriage in pharyngeal swab samples is unclear. While it has been explored as an alternative to the capsule transport A gene for detecting invasive strains, its potential as the sole target for real-time PCR in meningococcal carriage screening remains unexplored. This study aimed to assess the utility of using sodC as a target for detecting invasive and non-invasive strains of Neisseria meningitidis in pharyngeal swabs. Oropharyngeal swab samples collected from adolescents (approximately 15–18 years of age) enrolled in the “B-Part-of-It” cluster-randomized controlled trial (NCT03089086) were selected for this study. Samples were initially screened for the presence of specific N meningitidis porin A gene (porA) using PCR and then preserved by freezing at −80°C. An assay targeting the sodC gene was developed using the locked nucleic acid probe-based method. Upon optimization of the sodC assay, 1,092 samples were retested using this assay and compared against the results from the porA assays to determine concordance. Out of 1,092 samples tested, 965 (88.4%) were sodC positive, with 100% sensitivity and 13% specificity compared to porA. The positive predictive values and negative predictive values for the sodC assay were 12% and 100%, respectively. When compared to porA PCR as the gold standard, the sodC assay lacks sufficient specificity to serve as a stand-alone screening assay for the detection of Neisseria meningitidis carriage in pharyngeal samples from adolescents.IMPORTANCEWhile the sodC assay successfully detects N. meningitidis, we identified a limitation in its specificity due to potential cross-reactivity with other organisms, including Haemophilus spp., which can result in false positives. This limitation highlights the need for careful interpretation of Neisseria meningitidis carriage results, especially in epidemiological studies.